Studies of middle atmosphere dynamics under the Polar Patrol Balloon (PPB) project: Present status and future plans - Yamanaka, Manabu D.; Yamazaki, Koji; Kanzawa, Hiroshi (National Institute of Polar Research, 1988)
P(論文) Studies of middle atmospheric dynamics under the PPB project have two aspects. On one hand, they are necessary to predict a feasibility of PPB flight. Recent studies on global-scale disturbances (planetary waves) over the Antarctic stratosphere suggest that the mid-summer (December-January) flight at 30-40km altitudes has a trajectory with meridional fluctuations with ±2° around the initial latitude. The mid-winter (June-August) flight in the Antarctic stratosphere may be much circumpolar than that in the Arctic. The spring (October-November) and autumn (February) flights are not adequate for circumpolar observations. We predict that the north-south drift due to small-scale disturbances (gravity waves) may be within ±0.3°, although this must be confirmed in the future. On the other hand, trajectory analysis and balloon-borne anemometry of PPB would give us useful information for studying the transport process and the gravity-wave effect in the Antarctic stratosphere. departmental bulletin paper